Assessment of Factors Associated with Prehospital Delay of Patients with Acute Myocardial Infarction - Jasser, saad; hassan, Hakima (Iraqi National Journal of Nursing Specialties, 2011)
Objective(s): to assess the factors which are associated with the prolonged prehospital delay of patients with acute myocardial infarction. Methodology: A descriptive study was conducted at the Coronary Care unit (CCU) in Al-Yarmok Teaching Hospital, Ibn AL-Nafis Hospital for Cardiovascular Diseases, AL-Kadumia Teaching Hospital, Baghdad Teaching Hospital, and AL-Kindy Teaching Hospital during the period of the study from February 2 nd , 2009 to October 30th , 2009. A random sample of (160) paƟent who were admiƩed to the hospitals were selected one by one. A questionnaire was constructed for the purpose of the study, which is comprised of four parts that include (1) sociodemographic data; (2) prehospital delay time was measured as the time which passed from the moment when the patient feels the first symptoms "chest pain" until his arrival to the Coronary Care Unit (CCU) (3) clinical data; (4) factors associated with the prolonged prehospital delay. The data were collected by the application of the questionnaire, the interview technique, observation and the patients’ sheets. Results: The study findings indicated that the low percentage of the patients with myocardial infarction used an ambulance (3; 1.9%) and the remaining (157; 98%) arrived at hospitals by self-transport. It is concluded that a large proportion of Iraqi patients did not call for an ambulance after the onset of ST–Elevation Myocardial Infarction (STEMI) symptoms. Recommendations: The study recommends that the public should be educated that an ambulance is not merely a transportation modality, but also a means of providing early diagnosis and treatment.